Komunikasi Pemasaran Jasa Pendidikan - Moh. Turmudi; Sun Fatayati (Universitas Islam Tribakti Lirboyo Kediri, 2021)
Communication is the key to marketing success, including marketing educational services. Marketing communication is an integral part of communication and also an integral part of marketing. The literature method is used; data is taken through online source searches, books and articles in scientific journals. While analyzing it, the analysis content is used as a technique in analyzing it. As a result, communication marketing of educational services is a two-way information exchange between parties involved in educational service marketing activities in schools to improve the customer's image of educational products. And to maintain its existence, educational institutions must be more creative in packaging the promotion or communication of educational services adapted to the challenges of today's times